Structural and Functional Insights Into Lysostaphin–Substrate Interaction - Tossavainen, Helena; Raulinaitis, Vytas; Kauppinen, Linda; Pentikäinen, Ulla; Maaheimo, Hannu; Permi, Perttu (Frontiers in Molecular Biosciences, 2018)
Lysostaphin from Staphylococcus simulans and its family enzymes rapidly acquire prominence as the next generation agents in treatment of S. aureus infections. The specificity of lysostaphin is promoted by its C-terminal cell wall targeting domain selectivity toward pentaglycine bridges in S. aureus cell wall. Scission of these cross-links is carried out by its N-terminal catalytic domain, a zinc-dependent endopeptidase. Understanding the determinants affecting the efficiency of catalysis and strength and specificity of interactions lies at the heart of all lysostaphin family enzyme applications. To this end, we have used NMR, SAXS and molecular dynamics simulations to characterize lysostaphin structure and dynamics, to address the inter-domain interaction, the enzyme-substrate interaction as well as the catalytic properties of pentaglycine cleavage in solution. Our NMR structure confirms the recent crystal structure, yet, together with the molecular dynamics simulations, emphasizes the dynamic nature of the loops embracing the catalytic site. We found no evidence for inter-domain interaction, but, interestingly, the SAXS data delineate two preferred conformation subpopulations. Catalytic H329 and H360 were observed to bind a second zinc ion, which reduces lysostaphin pentaglycine cleaving activity. Binding of pentaglycine or its lysine derivatives to the targeting domain was found to be of very low affinity. The pentaglycine interaction site was located to the N-terminal groove of the domain. Notably, the targeting domain binds the peptidoglycan stem peptide Ala-d-γ-Glu-Lys-d-Ala-d-Ala with a much higher, micromolar affinity. Binding site mapping reveals two interaction sites of different affinities on the surface of the domain for this peptide.